Public Land Disputes in Vietnam: A Multi-Actor Analysis of Five Case Studies with an East Asian Comparative - John Gillespie; John Gillespie
The studies consider not only the formal policies and procedures applicable and/or employed in these disputes but also the perspectives and actions of citizens, businesses, investors, the media, mass organizations, and government officials. Case studies were selected for geographic and economic diversity and involve rural, peri-urban, and urban communities. The cases also vary in their level of private investor involvement and the intensity of the dispute.